Effects of bioactive constituents in Musa x paradisiaca flower on milk production in vivo - Mahmood, Azizah; Omar, Muhammad Nor; Ngah, Nurziana (2011)
Many plants are reputed to possess galactagogue activity that can be consumed to increase milk production for the need of the young. These plants should have contained possible substances that interact and affect lactation in mothers. In this research, two compounds (C1 and C2) were extracted from Musa x paradisiaca flower to determine its effect on milk production. 30 lactating rats of Spraque Dawley strain were daily administered with samples started from Day 5 through Day 15 of lactation using feeding tubes. The performance of milk production was measured by means of weight-suckle-weight method after a 6 hrs separation of litters. Results of the studied compounds were statistically analyzed and compared to the aqueous crude extract, metachlopromide and control group using SPSS by means of ANOVA at 0.01 level of significant. Milk production of C1 and aqueous crude extract groups were significantly higher compared to C2, metachlopromide, and control groups. C1 was identified to increase milk production by 28.03%, while aqueous extract by 24.87%. The mean of milk yield within the given suckling period in gram of crude extract, C1, metachlopromide, C2 and control group were 4.86, 4.65, 3.76, 3.68 and 3.63 respectively. The lactation time of the experimental groups was either at Day 13 or Day 14 of lactation period. It was concluded that the bioactive compound (C1) exist in the flower could be the possible compound which affected milk production.